Implementasi Kurikulum Merdeka di Taman Kanak-kanak - Andi Al Muhammad Ardiansyah; Ismail, Tolla; Azizah, Amal; Gusnaini; Sumarni; Hilda, Sofiana (Ihya Ulum: Early Childhood Education Journal, 2023)
This research aims to find out the description of the implementation of the independent curriculum as well as the supporting and inhibiting factors. The resource persons of this research are 2 teachers and 1 principal. The research method used is descriptive qualitative using observation, interviews, and documentation as data collection techniques. The results of the analysis showed that As' Adiyah Lompengeng Kindergarten was initially selected as a driving school and was required to use the independent curriculum. The teaching tools used are obtained from the government and have been developed by the school before use such as teaching modules, P5 modules, and guidebooks for teachers. Learning is divided into intracurricular, co-curricular, and extracurricular. The development of the Pancasila profile is carried out with project activities, namely with the theme I love Indonesia and with the topic of making typical bugis cakes that are not cooked. The assessments carried out are diagnostic assessments during PPDB, formative assessments during learning, and summative assessments at the end of the semester. The conclusion of this study is that the implementation of the independent curriculum at As' Adiyah Lompengeng Kindergarten, Soppeng Regency is going well because the teachers and Principal have a good understanding of the independent curriculum and thanks to the support of the government even though there are still obstacles experienced.